Inside Biosphere 2 : earth science under glass - Carson, Mary Kay (Scientists in the field., 2015)
Examines the construction and original purpose of the Biosphere 2 in Arizona, the ecosystems inside, the scientists working within the structure, and the results of the two-year experiment. Also describes how scientists today use the Biosphere 2 to study the effects of climate change. Includes dozens of color photographs and diagrams, a glossary, and further resources.